DESENVOLVIMENTO DE UM SENSOR DE UMIDADE DO SOLO PARA DETERMINAÇÃO DA FRENTE DE MOLHAMENTO - Cruz, João Alexandre Batista da (2013)
The knowledge and control of soil properties in gricultural cultivation, obtained from sensors at automated system, extend the possibilities of increasing the results of a culture. This work aims to develop an electrical measure sensor at low cost to determinethe soil moisture, test and evaluate the correlation between the readings and gravimetric soil moisture, considered standard to calibratethe other methods. To achieve the proposed objective, in the first place we sought to study the main aspects of the interaction process water-soil-plant and the existing methods of determination. Subsequently, we performed the fabrication of prototype sensors in different shapes and geometry. We have also developed a measurement and record systemthat enables us to collect the data and to store them in a memory card. Having the operation of the sensors as a beginning, the concept of capacitance is obtained by the effect of the electric field, the charge of two plates insulated by a dielectric material, which, therefore, in this study is the soil moisture. Thus, when there is a variation in the dielectric constant, depending on the amount of water present in it, the capacitance of the system will also vary. Finally, tests were performed to evaluate the sensors and circuitry construction. The results were satisfactory, with a correlation coefficient of 99.14% for a non conventional coplanar plates sensor.